Green sustainable process for chemical and environmental engineering and science : plant-derived green solvents : properties and applications - Inamuddin, 1980-; Boddula, Rajender; Asiri, Abdullah M. (Elsevier, 2021)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Plant-Derived Green Solvents: Properties and Applications provide a comprehensive review on the green solvents such as bio solvents, terpenes, neem, alkyl phenols, cyrene, limenone, and ethyl lactate, etc. which are derived from plant sources. Chapters discuss introduction, properties, and advantages to the practical use of plant-derived solvents. Plants-derived solvents are an excellent choice for real-world applications to reduce the environmental and health safety considerations. This book is the result of commitments by top researchers in the field of biosolvents from various backgrounds and fields of expertise. This book is a one-stop reference for plant solvents and overviews up-to-date accounts in the field of modern applications and the first book in this research community.